EFFECTS OF STAGNATION REGION TURBULENCE OF AN IMPINGING JET ON HEAT TRANSFER - Celik, Nevin; Eren, Haydar (Turkish Soc Thermal Sciences Technology, 2010)
In the present study, heat transfer and flow dynamics effects of an impinging jet are experimentally investigated. Contrary to many performed work in literature, a pipe having a large diameter is used as a nozzle, to show the large diameters' effect on heat transfer. The jet used in this study is a smooth aluminum pipe of 23.1 mm inner pipe and 25 mm outer pipe diameter. Jet impingement cooling of the flat plate, which is vertically placed and heated on its rear side by film condensation, is investigated by the terms of Nusselt number. Two effective factors on cooling; such as nozzle-plate distance (hid = 4-12) and Reynolds number (5000-25000), are chosen as variable parameters. Additionally, the turbulent intensity on the near field region of the impingement plate, which occurred when the jet is subjected to the plate, is measured by using a high sensitive air velocity transducer.
Keywords: Impinging jets; Heat Transfer; Turbulent intensity